2015
DOI: 10.3382/ps/peu041
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rearing environment on bone growth of pullets

Abstract: Alternative housing systems for laying hens provide mechanical loading and help reduce bone loss. Moreover, achieving greater peak bone mass during pullet phase can be crucial to prevent fractures in the production period. The aim of this study was to determine the housing system effects on bone quality of pullets. Tibiae and humeri of White Leghorn pullets reared in conventional cages (CCs) and a cage-free aviary (AV) system were studied. At 16 wk, 120 birds at random from each housing system were euthanized.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
57
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 19 publications
7
57
0
Order By: Relevance
“…The improved bone mechanical properties of aviary birds should be directly related to greater physical activity of these birds in this type of housing (Fleming et al, 2006) which have been confirmed during lay (Leyendecker et al, 2001;Regmi et al, 2016) and during rear (Regmi et al, 2015). Prolonged immobility in cage hens increases bone resorption whereas increased physical activity (as in aviary birds) stimulate bone formation and remodeling.…”
Section: Discussionmentioning
confidence: 82%
“…The improved bone mechanical properties of aviary birds should be directly related to greater physical activity of these birds in this type of housing (Fleming et al, 2006) which have been confirmed during lay (Leyendecker et al, 2001;Regmi et al, 2016) and during rear (Regmi et al, 2015). Prolonged immobility in cage hens increases bone resorption whereas increased physical activity (as in aviary birds) stimulate bone formation and remodeling.…”
Section: Discussionmentioning
confidence: 82%
“…As previously demonstrated CT scanning is a useful research tool to study the morphology and the number of fractures and exact location [37]. CT scanning allows the investigation of the external appearance of the fractures thought the 3D models, as well accurate inspection of what happened inside the bone.…”
Section: Discussionmentioning
confidence: 99%
“…The human capital approach is a key economic rationale for the policy makers to enhance the national investment in education to widen individuals' participation in the education (Gale & Molla, 2015). The human capital theory explains that national investment in education and training for developing competent citizens is positively associated with economic growth (Dean, 2003;Regmi et al, 2015). The "education" as a strategy of economic revival attracted the significant attention of policy makers after the 2008 Global Financial Crisis (Antolin & Stewart, 2009).…”
Section: Tvet and Economic Growthmentioning
confidence: 99%
“…The "education" as a strategy of economic revival attracted the significant attention of policy makers after the 2008 Global Financial Crisis (Antolin & Stewart, 2009). The human capital theory provides a perspective of the education as a capital good for developing human resources to cope with socioeconomic changes (Olaniyan & Okemakinde, 2008;Regmi et al, 2015). The human capital outcomes resulting from the imperative role of educational institutions (Biesta, 2006) as the engine for economic growth (Gowlett, 2012) are driving the recent educational policies (Walker, 2012).…”
Section: Tvet and Economic Growthmentioning
confidence: 99%